Contribution of health status and prevalent chronic disease to individual risk for workplace injury in the manufacturing environment. Issue 3 (16th October 2013) - Kubo, Jessica; Goldstein, Benjamin A; Cantley, Linda F; Tessier-Sherman, Baylah; Galusha, Deron; Slade, Martin D; Chu, Isabella M; Cullen, Mark R
Abstract : Objectives: An 'information gap' has been identified regarding the effects of chronic disease on occupational injury risk. We investigated the association of ischaemic heart disease, hypertension, diabetes, depression and asthma with acute occupational injury in a cohort of manufacturing workers from 1 January 1997 through 31 December 2007. Methods: We used administrative data on real-time injury, medical claims, workplace characteristics and demographics to examine this association. We employed a piecewise exponential model within an Andersen–Gill framework with a frailty term at the employee level to account for inclusion of multiple injuries for each employee, random effects at the employee level due to correlation among jobs held by an employee, and experience on the job as a covariate. Results: One-third of employees had at least one of the diseases during the study period. After adjusting for potential confounders, presence of these diseases was associated with increased hazard of injury: heart disease (HR 1.23, 95% CI 1.11 to 1.36), diabetes (HR 1.17, 95% CI 1.08 to 1.27), depression (HR 1.25, 95% CI 1.12 to 1.38) and asthma (HR 1.14, 95% CI 1.02 to 1.287). Hypertension was not significantly associated with hazard of injury. Associations of chronic disease with injury risk were less evident for more serious reportable injuries; only depression and a summary health metric derived from claims remained significantly positive in this subset. Conclusions: Our results suggest that chronic heart disease, diabetes and depression confer an increased risk for acute occupational injury.